KERAGAMAN GENETIK POPULASI ALAM MATOA (Pometia pinnata Forst.) DI PAPUA BARAT BERDASARKAN PENANDA ISOENZIM - , Alexander Rumatora, Prof. Dr. Ir. Moh. Naâiem, M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Isoenzyme analysis was performed on four populations of matoa papeda (Pometia pinnata Forst.) original from West Papua, i.e. Manokwari, Sorong, Fak- Fak and Raja Ampat. The goals were to determine the inheritance of banding patterns, to assess genetic diversity of natural populations, and to know the genetic relationship among populations. Leaves were sampled from 25 seedlings in each populations and analyzed using isoenzime markers. Three of six enzyme systems showed polymorphic and consistent activities, and can be used to observe genetic diversity of matoa, namely: Peroxidase (POD), Esterase (EST), Glutamate Oxaloacetate Transaminase (GOT). Effective number of alleles per locus (Ae=1.9549) is lower than actual number of alleles per locus (A/L=2.5). Obseved heterozygosities (Ho) ranged from 0.4266 (Fak- Fak) up to 0,4831 (Raja Ampat), with the average of 0.4491. Expected heterozygosities (He) ranged from 0.4541 (Sorong) up to 0.5399 (Fak-Fak), with the average 0.4669. The total genetic diversity (HT) at the fourth matoa population was 0.504, mostly distributed within (HS=0.457) and the rest (DST =0.047) distributed among populations, with the proportion of genetic diversity between populations (GST = 0.111). Populations of Manokwari and Sorong hare closest genetic relationship, while Raja Ampat showed most distance to other three populations.